Numerical investigation on pitch distance, compound angle and turbulence intensity of double cylindrical film cooling hole geometry - Aminnuddin, Hazim Fadli; Abdullah, Mohammad Kamil (Asian Research Publishing Network (ARPN), 2017)
Film cooling has been extensively used to provide thermal protection for the external surface of the gas turbine blades. Researchers have introduced numerous number of film cooling hole designs and arrangements with aim to reduce the lift-off effect cause by the counter rotating vortex pair (CRVP) produced in the cylindrical cooling hole configuration. Such efforts include the introduction of coupling film cooling designs. The present study focuses on the coupling holes which will later known in this writing as Double Cylindrical Hole (DCH). Two geometrical parameters have been considered; length between holes, PoD and compound angle,